Introduction to the special issue "Digital mortality: Death and infrastructure". Issue 3 (27th May 2022) - Graham, Connor; Pang, Natalie; Willems, Thijs
Abstract: Prior internet studies research has examined dying, death, and disposal from the perspectives of material practices, new persistences, visibilities, and identities, but less so through the lens of platforms and algorithms. This special issue examines how digital infrastructures, manifested as platforms and algorithms, function to transform experiences of mortality and mortal existences. It opens up discussion about the ways in which intersections of death and digital formations produce and inflect experiences and representations of the body and place, providing fresh analytical insight into and through the concept of digital mortality. In doing so, it reflects on the dialogical relationship between digital infrastructure and mortality, and how digital infrastructure transforms meanings of mortality and death. Inverting prior emphases on the internet and media as transforming death, it shows the value of studying and questioning digital infrastructure through the concept of mortality.